2008
DOI: 10.1111/j.1744-6155.2008.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis of Risk Factors That Predict Psychopathology Following Accidental Trauma

Abstract: Information gathered from such meta-analyses could be used in the identification of at-risk children and the development of screening tools. However, further widespread and comprehensive reviews of the potential risk factors and their relationships to psychopathology need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
105
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 52 publications
11
105
2
1
Order By: Relevance
“…Limitations of this study include the lack of information on pre-injury behavioural functioning that prevented to examine a causal relationship between the burn event and postburn child problems. In other studies after accidental trauma [13,46], pretrauma behaviour was strongly linked to behaviour after traumatic injuries. In general, it is difficult to gather reliable (parent-reported) information concerning child pre-injury behaviour problems once admitted to the hospital, but it should nevertheless be a point of attention.…”
Section: Discussionmentioning
confidence: 75%
“…Limitations of this study include the lack of information on pre-injury behavioural functioning that prevented to examine a causal relationship between the burn event and postburn child problems. In other studies after accidental trauma [13,46], pretrauma behaviour was strongly linked to behaviour after traumatic injuries. In general, it is difficult to gather reliable (parent-reported) information concerning child pre-injury behaviour problems once admitted to the hospital, but it should nevertheless be a point of attention.…”
Section: Discussionmentioning
confidence: 75%
“…Also of note, traumatic injuries incurred before 2001 were independently associated with an increased risk of postinjury psychiatric diagnoses and psychotropic medication prescription. Prior reports suggest that pre-event psychopathology and recurrent trauma among youths and their family members are associated with an increased risk of developing PTSD and related psychiatric disorders (1,21,22,30,55). These collective findings suggest that postinjury screening and intervention protocols in acute care and pediatric practice settings may need to target high-risk children and adolescents who have been exposed to multiple injury events or who have a history of psychiatric disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In warfare studies of PTSD in children, incidence rates between 25% to 70% are reported depending on type of exposure and type of warfare [2,22]. A number of studies have reported level of exposure and trauma severity as two main risk factors of PTSD [12,[23][24][25]. Trickey and colleagues [5] have identified trauma severity as the trauma characteristic most strongly associated with risk of PTSD in children and adolescents but suggest that trauma severity may be difficult to differentiate from trauma exposure.…”
Section: The Omagh Bombingmentioning
confidence: 99%
“…There have also been conflicting findings regarding the relationship between gender and PTSD with some studies recording PTSD in girls at twice the rate as in boys [7]. Whist several studies have reported gender as a significant risk factor [12,21,24,29,32], Trickey and colleagues [5] reported female gender to be a consistent although statistically small risk factor and a stronger risk factor in older children and adolescents and also when the trauma is unintentional. Whilst girls seem more vulnerable to internalizing stress reactions, boys display more externalizing behaviour disturbance [24,33].…”
Section: The Omagh Bombingmentioning
confidence: 99%
See 1 more Smart Citation